INCLUSIVE LEGAL POSITIVISM: BASIC ARGUMENTS - Didikin, A.B. (Право и государство № 3 (100), 2023)
The relevance of the topic of this paper is due to the insufficient study of the problems of inclusive legal positivism in the modern philosophy of law. The problem of substantiating the thesis of the inclusion of morality in law on the basis of rational argumenta- tion of scientists and legal practice data considered in the paper allows an innovative analysis of basic legal concepts. The subject of the research is to analyze the methods of moral, ethical and legal argumentation in the works of representatives of inclusive legal positivism. The purpose of the work is to theoretically reconstruct the essence of the debate between inclusive and exclusive legal positivism. The novelty of the topic is due to the lack of studies in the educational and scientific literature on the specifics of the argumentation of inclusive legal positivism, set out in the scientific works of Will Waluchow and Kenneth Himma, the need to rethink traditional ideas about the theory of legal positivism. The research methods used in the paper is the methods characteristic of analyt- ical jurisprudence, including those related to the use of methods of logical and linguistic analysis, as well as special legal methods (formal legal method of interpretation of regulatory prescriptions). The main conclusions of the paper are to reveal the key arguments of the concept of inclusive legal positivism. It is proved that from the point of view of this concept, the law has moral grounds, and judges in some cases use moral reasoning when making court de- cisions.
Keywords: inclusive legal positivism; normative prescriptions; moral foundations of law; moral obligations; judicial practice; judicial discretion; W. Waluchow, K. Himma